2019
DOI: 10.1177/1179547619867330
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Epstein-Barr Virus–Associated Leiomyosarcoma Concurrently With Posttransplant Lymphoproliferative Disorders After Renal Transplantation

Abstract: Epstein-Barr virus (EBV) infection might induce not only posttransplantation lymphoproliferative disorder (PTLD) but also leiomyosarcoma. We report a case of EBV-associated leiomyosarcoma concurrently with PTLD after renal transplantation. The patient was a 30-year-old woman who underwent living donor kidney transplantation at 27 years of age. Preoperative EBV viral capsid antibody immunoglobulin M, immunoglobulin G (IgG), and EBV nuclear antigen IgG were negative. Multiple lung and liver tumors were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This encodes all of the enzymes involved in the replication of its DNA and in nucleotide biosynthesis 60 . It has been linked to a number of malignancies, such as Hodgkin's disease 61 , B-and T-cell lymphomas 62 , leiomyosarcomas 63 , post-transplant lymphoproliferative disease 64 , and nasopharyngeal carcinomas 65 . Among all of these cancers, the frequency of Burkitt's lymphoma, leiomyosarcomas and posttransplant lymphoproliferative disease have dramatically increased in the past few years especially in patients who suffer from immunodeficiency, revealing the role of immunosurveillance in the prevention and suppression of malignant transformation 66 .…”
Section: Carcinogenic Virusesmentioning
confidence: 99%
“…This encodes all of the enzymes involved in the replication of its DNA and in nucleotide biosynthesis 60 . It has been linked to a number of malignancies, such as Hodgkin's disease 61 , B-and T-cell lymphomas 62 , leiomyosarcomas 63 , post-transplant lymphoproliferative disease 64 , and nasopharyngeal carcinomas 65 . Among all of these cancers, the frequency of Burkitt's lymphoma, leiomyosarcomas and posttransplant lymphoproliferative disease have dramatically increased in the past few years especially in patients who suffer from immunodeficiency, revealing the role of immunosurveillance in the prevention and suppression of malignant transformation 66 .…”
Section: Carcinogenic Virusesmentioning
confidence: 99%
“…Several cases of EBV‐related LMS in immunosuppressed patients have been reported 25,29,39,56–98 . LMS in immunosuppressed patients after organ transplantation and in patients with human immunodeficiency virus (HIV) is associated with EBV.…”
Section: Introductionmentioning
confidence: 99%
“…LMS in immunosuppressed patients after organ transplantation and in patients with human immunodeficiency virus (HIV) is associated with EBV. EBV‐associated LMS is common in children with HIV, and uncommon in adult patients with HIV 25,29,39,56–98 . Marioni et al 19 reported LLMS in a patient with two kidney transplants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations